Effect of Freeze-Thaw Cycle on Anchor Fracture Load in Carbonate Rocks - Çetinta?, Sevgi; Serpinli, Sercan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Natural stone is widely used as a cladding material in the construction sector due to its durability and aesthetic appearance. When anchoring natural stone to building exteriors, it is of great importance to consider the mineralogical and mechanical properties of the stone. This study examines the changes in the breaking loads at the dowel holes of different carbonate stones used as cladding material in relation to freeze-thaw cycles and identifies the relationship of such changes with the physical and mechanical properties of the samples. For this purpose, four different types of natural stones were acquired, and the breaking loads at the dowel holes of the stone samples were analyzed according to standard procedures after being subjected to 25 freeze-thaw cycles. Mineralogical, petrographic, physical and mechanical characteristics of the stone samples were identified. It was shown that the breaking load values obtained at the anchorage points decreased due to the freeze-thaw cycles, and that the physical, mechanical and mineralogical characteristics of the sample had an effect on breakage.